Data Analysis for Robotics and Programming Project Evaluation Involving Female Students Participation - Ferreira, Maria; Lima, Danielli; Silva, Aline (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2019: Anais do VII Simpósio Brasileiro de Robótica e XVI Simpósio Latino Americano de Robótica, 2019)
Educational robotics is an example of building an innovative and effective educational model in its proposal. The model in question consists in the creation of learning environments that bring together assembly materials composed of diverse, interactive and computer controllable parts through programming. It is possible to control the functioning of assembled prototypes. This interaction creates interest and direct involvement by students, and can integrate with other knowledge areas, developing activities in the interdisciplinary context, in which students experience in a practical way and directly apply the contents viewed theoretically in the classroom. However this area is mostly dominated by male students. Thus, the objective of this paper is to present a study case discussion of a robotics and programming project whose objective is to increase girl project participation and from there, to encourage these students to pursue careers in science, technology and engineering. The data were treated through data mining for further analysis, and the results are promising regarding the interaction of these student girls with the project and with the robotics and programming areas applied to education and competition.